Service Systems Implementation - Demirkan, Haluk; Spohrer, James C.; Krishna, Vikas; SpringerLink (Online service). (Boston, MA Springer US, 2011)
Service Systems Implementation provides the latest applications and practices aimed at improving the key performance indicators of service systems, especially those related to service quality, service productivity, regulatory compliance, and sustainable service innovation. The book presents action-oriented, application-oriented, design science-oriented (artifacts building: constructs, models, methods and instantiations) and case study-oriented research with actionable results by illustrating techniques that can be employed in large scale, real world examples. The case studies will help visualize service systems along the four key dimensions of people, information, technology and value propositions which can help enable better integration between them towards higher value propositions. The chapters, written by leading experts in the field, examine a wide range of substantive issues and implementations related to service science in various industries. These contributions also showcase the application of an array of research methods, including surveys, experiments, design science, case studies and frameworks, providing the reader with insights and guidelines to assist in building their own service systems, and thus, moving toward a more favorable service customer and provider experience. Service Systems Implementation, along with its companion text, The Science of Service Systems, is designed to present multidisciplinary and multisectoral perspectives on the nature of service systems, on research and practice in service, and on the future directions to advance service science. These two volumes compose a collection of articles from those involved in the emerging area known as service science.
Data-Driven Simulation-Enhanced Optimization of People-based Print Production Service -- Intelligent Document Gateway - A Service System Case Study and Analysis -- A Framework for the Design of Service Systems -- Surviving Nuclear Winter - Towards a Service-Led Business -- Towards an Operations Strategy for the Infusion of Product-Centric Services into Manufacturing -- Theory of Constraints for Services: Past, Present, and Future -- An assessment tool for establishing Infrastructure as a Service Capability Maturity -- Customer-Provider Strategic Alignment: A Maturity Model -- CIO in a Service Economy -- Service Productivity: How to Measure and Improve It? -- Value Co-Creation from the Consumer Perspective -- Metrics that Matter - Measuring and Improving the Value of Service -- Succeeding through Service Innovation: Consumer Directed Care in the Aged Care Sector -- Measurement In Service Businesses: Challenges and Future Directions -- An Integrated View of Service Innovation in Service Networks -- A Service Systems Perspective of E-government Development -- Predictive Systems for Customer Interactions.
Electronic reproduction.
Keywords: Service industries; Industrial management; Electronic books